2016
DOI: 10.4995/wrs.2016.4025
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate peel as a natural antioxidant enhanced reproductive performance and milk yield of female rabbits

Abstract: This study was designed to investigate the effects of dietary pomegranate peel (PP; 9.61% crude protein and 13.1% crude fibre) on reproductive performance and milk yield of heat-stressed rabbit does. Forty-eight V-line rabbit does with average initial live body weight of 3.59±0.11 kg (2 nd parity; 9 mo old) were divided into 4 treatment groups (12 does per group). The first group was fed diet free of PP. The second, third and fourth groups were fed diets containing 0.75, 1.5 and 3.0% PP, respectively, included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Dietary manipulation has been identified as the most affordable method of alleviating the negative effect of high ambient temperature in the tropics, as the high cost of cooling animal pens is unaffordable W o r l d R a b b i t S c i e n c e for farmers (Konca et al, 2009). Therefore, the use of diets rich in natural antioxidants as a means of removing excessive free radicals from the animal's body and consequent alleviation of high-temperature negative effects on animal production is becoming popular (Liu et al, 2010;Kone et al, 2016;Zeweil and Elgindy, 2016;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary manipulation has been identified as the most affordable method of alleviating the negative effect of high ambient temperature in the tropics, as the high cost of cooling animal pens is unaffordable W o r l d R a b b i t S c i e n c e for farmers (Konca et al, 2009). Therefore, the use of diets rich in natural antioxidants as a means of removing excessive free radicals from the animal's body and consequent alleviation of high-temperature negative effects on animal production is becoming popular (Liu et al, 2010;Kone et al, 2016;Zeweil and Elgindy, 2016;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PBP had a higher CF content (19.71% vs. 11.43%). In this connection, Zeweil and El-Gindy (2016) reported that pomegranate peel contained 90.00, 82.12, 9.61, 2.35, 13.07, 57.09 for dry matter, organic matter, crude protein, ether extract, crude fiber, nitrogen free extract.…”
Section: Chemical Analysis Of Pomegranate By-product Powdermentioning
confidence: 96%
“…In this connection. Zeweil et al (2016) stated that the total phenolic content of pomegranate peel was 272 mg GAE /g DM. Moreover, Azoz and Basyony (2012) reported that total phenolic content was 270 mg GAE / g Dry weight of this pomegranate by-product.…”
Section: Chemical Analysis Of Pomegranate By-product Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is not economical and even hardly feasible to raise animals without them reproducing, overcoming challenges of oxidative damages associated with reproduction is highly desirable. [14,27,45] Oxidative balance as presented in Figure 1 when triggered cause damages in reproductive activities in animals and human being. Major problems of reproductive performance associated with oxidative stress damage are infertility in female human subjects while in male subjects; it reduces fertilizing capabilities of sperm.…”
Section: Functional Biochemical Process Of Oxidative Stressmentioning
confidence: 99%